Image-based multiplex immune profiling of cancer tissues: translational implications : a report of the International Immuno-oncology Biomarker Working Group on Breast Cancer - Jahangir, Chowdhury Arif; Page, David B; Broeckx, Glenn; Gonzalez, Claudia A; Burke, Caoimbhe; Murphy, Clodagh; Reis-Filho, Jorge S; Ly, Amy; Harms, Paul W; Gupta, Rajarsi R; Vieth, Michael; Hida, Akira I; et al. (The journal of pathology, 2024)
Recent advances in the field of immuno-oncology have brought transformative changes in the management of cancer patients. The immune profile of tumours has been found to have key value in predicting disease prognosis and treatment response in various cancers. Multiplex immunohistochemistry and immunofluorescence have emerged as potent tools for the simultaneous detection of multiple protein biomarkers in a single tissue section, thereby expanding opportunities for molecular and immune profiling while preserving tissue samples. By establishing the phenotype of individual tumour cells when distributed within a mixed cell population, the identification of clinically relevant biomarkers with high-throughput multiplex immunophenotyping of tumour samples has great potential to guide appropriate treatment choices. Moreover, the emergence of novel multi-marker imaging approaches can now provide unprecedented insights into the tumour microenvironment, including the potential interplay between various cell types. However, there are significant challenges to widespread integration of these technologies in daily research and clinical practice. This review addresses the challenges and potential solutions within a structured framework of action from a regulatory and clinical trial perspective. New developments within the field of immunophenotyping using multiplexed tissue imaging platforms and associated digital pathology are also described, with a specific focus on translational implications across different subtypes of cancer. © 2024 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.
Gesehen am 25.10.2024